En attraktiv arbetsplats : En väg till att uppfattas som en attraktiv arbetsgivare av befintlig och framtida arbetskraft - Vikander, Lillemor (2012)
Luleå is, like so many other employers, facing a major generational change in the coming years. A large number of retirements, results in a need to recruit around 500 people annually over the next few years and projections indicate that the generation that will replace the labor market is smaller than the one that leaves. In the competition expected to arise, an employer have to be able to offer an attractive workplace, both to retain existing workforce and also to attract the future workforce. This study aims to compare the requirements of future labor set in an attractive workplace with regard to the views Luleå municipality employees have about their workplace in order to thus find suggestions that could lead to a workplace that is attractive to both existing and future workforce. This is done through a comparison of a survey with Luleå university students, who in this study represent the future workforce, and Luleå municipality's employee-survey in 2011, and additional interviews with employees at higher organizational levels.The results showed that employees give high marks in many of the factors that students want to see in a future employer. Employees also suggest a good job satisfaction and meaningful work. In all Luleå municipality offers its employees an attractive workplace. Nonetheless Luleå municipality is not seen as an employer of choice, either by students or employees. One possible reason could be an outdated approach to public sector as sluggish, slow and inefficient. To change that image Luleå municipality needs work with their employer brand. The study suggests that the organization should begin to strengthen its brand from the inside by improving the shortcomings employee survey shows, as well as to highlight and market the strengths that exist. Satisfied and proud employees act as ambassadors for an attractive employer. Validerat; 20120618 (anonymous)